The Cross as the Path to Christian Perfection According to St. Louis-Marie Grignion de Montfort (1673–1716) - Klauza, Aleksandra (Studia Teologiczne Białystok Drohiczyn Łomża, 2025)
The aim of this article is to present the teaching of the cross in the works of St. Louis-Marie Grignion de Montfort. In his writings, the cross is not merely a symbol of suffering, but a path to deep union with Christ—a way of love, purification, and salvation. The French saint shows that accepting the cross in the daily life of a Christian does not mean passive resignation, but an active response to God’s love, which was most fully revealed in the sacrifice of Christ. The analyses conducted indicate that Montfort does not offer easy answers to the problem of suffering—he neither eliminates nor simplifies it, but instead points to its meaning in the light of Jesus’ cross. The cross becomes a school of humility, a tool of sanctification, and a path to Christian perfection. The acceptance of the cross, united with love for God, transforms pain into spiritual fruit and makes the soul capable of a deeper dedication to God.